Comparative analyses of competitive advantage using Porter diamond model (the case of MSMEs in Himachal Pradesh). Issue 2 (20th March 2017) - Kharub, Manjeet; Sharma, Rajiv
Abstract : Purpose: The purpose of this paper is to measure and analyze the competitive advantage of micro, small and medium enterprises (MSMEs) based upon the Porter's diamond framework. The major objective is to contribute toward better understanding of various determinants of the diamond model in context within Indian MSMEs. Design/methodology/approach: Extent review of the literature has been done to identify various critical factors contributing to developing a competitive advantage. Exploratory factor analysis and internal consistency tests were performed to verify scales validity and reliability of measuring instrument (questionnaire). In research design, a case study approach has been used, in which MSMEs operating in the pharmaceutical, electrical and electronics, automobile, food and textile sectors were considered. Findings: Study findings indicate that the pharmaceutical sector is more competitive followed by food (112.491) as revealed by the high value of surface area i.e. 150.931. The competitiveness among MSME sectors is mostly affected by demand conditions followed by firm strategy, structure and rivalry. Moreover, the score of diamond axes indicates significant difference with respect to determinants. For instance, in the textile sector, the determinants such as factor conditions and related and supporting industries scored low, for example, 4.710 and 4.280, respectively, which indicates it needs to be strengthened as this sector stands at last position with minimum surface area, for example, 67.398. Research limitations/implications: Owing to the time and resource constraints, this study was conducted in MSMEs situated in the state of Himachal Pradesh, India, and thus generalizations of results are rather limited. Practical implications: This study is one of the original being undertaken by authors which helps to underline the importance of various determinants which may help the MSME units to improve competitiveness by implementing effective competitive strategies. The study could be extended to other regions of the country. Originality/value: This study is a result of extended research on competitiveness and provides an instrument to measure firm ability to be competitive. CEO's, managers and policy makers from industries as well as government will be able to use this to evaluate their competitive positioning and identify key problem areas which required improvements.